PHYTOCHEMICAL SCREENING, TOTAL FLAVONOID, ANTIOXIDANT ACTIVITY, AND TOXICITY OF ETHANOL EXTRACT Cleome gynandra L. HERB - Widodo, Agustinus; Pratiwi, Ritha (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Cleome gynandra L. is one of the plants that the people of Palu, Central Sulawesi use as food ingredients. This plant is empirically used in traditional medicine. This study aims to determine phytochemical constituents, total flavonoid, antioxidant activity, and toxicity of 96% ethanol extract of C. gynandra herb. C. gynandra herb extract was obtained by maceration. Phytochemical screening of the ethanol extract was carried out qualitatively according to the standard methods. Determination of total flavonoid using AlCl3 then determined by Spectrophotometric UV-Vis. Antioxidant activity using the DPPH method and determined IC50 value. Toxicity test was assessed using shrimp lethality as an indicator of toxicity. Phytochemical screening showed 96% ethanol extract containing alkaloid compounds, flavonoids, saponins, steroids, and tannins. Total flavonoid of the 96% ethanol extract was 4,778 Â± 0,522 mg QE/g extract. Antioxidant activity (IC50) of the ethanol 96% extract was 189,455 Âµg/ml. Lethal concentration 50% of the 96% ethanol extract was 472,648 mg/L (toxic). The results of this study indicate that 96% ethanol extract of C. gynandra herb has antioxidant activity and has the potential to be further tested as an anticancer activity.